Limitaciones jurídicas del derecho a la resistencia y su necesidad de reforma - Ojeda Cabrera, Verónica Adriana (2015)
The Art. 283 of the Penal Code of Integral, defines and punishes the attack or resistance as a crime, but it is the case that the resistance considered a constitutionally guaranteed right to individuals, stated in Art. 98 of the Constitution of the Republic of Ecuador, in which individuals or groups may exercise the right of resistance against acts and omissions of public authorities, or non-state natural or legal persons who violate or may violate their constitutional rights and demand the recognition of new rights Integral Code to criminalize Pena, attack and resistance offense from the point of view of law latter goes against legal certainty, because on one hand, the Constitution recognizes the resistance as a right, but other criminal comprehensive legislation, is considered the resistance as an element of the offense, the person who attack or resist with violence or threats to public employees, trustees or agents of the police, the commissioners for the perception of taxes and contributions, the executors of decrees and judgments, the keepers of customs and revenue offices and police officers when held by law enforcement or orders or regulations made by public authority. Thus determined in the Penal Code of Integral legal rules are not clear and applied by the competent authority. The founding core values of the state, embodied in the Constitution, are weighing in organizing political coexistence and move around the legal system and make this a legal norm possessing an essentially different from the others, suffice it to say, qualitatively different the other rules of national law and gives some peculiar features. In this situation, the fundamentality of all constitutional rights is given by its resistance to legislative activity, as regards its essential contents. The legal assurance activity as need arises state model that limits public authorities to safeguard the fundamental rights which, in turn, being the property of universality which defines and makes them what they are derived to be the legal expression of the core values are dignity, freedom and equality of the person, giving the sense of legal activity, and determine their purpose. Fundamental rights, for that reason, are the way the law expresses the values that motivate the social contract as embodied by the issuance of a constitution